Portable Multi Capacitor Discharge Ignition Trainer to Enhance Students Critical Thinking Skills in Vocational High School - Marwanto, Eko; Safitri, Ria Rochmi; Surjono, Herman Dwi (Universitas Pendidikan Ganesha, 2024)
The low mastery of critical thinking skills results in students’ inability to interpret, analyze, and apply acquired knowledge. This condition adversely affects the mastery of competencies and decreases the competitiveness of vocational high school graduates. This study aims to develop the portable multi-CDI (Capacitor Discharge Ignition) system practice tool and test its effectiveness in improving students critical thinking skills in the competence of maintaining motorcycle ignition systems. To address the research questions, the study employs the ADDIE model for development research, which commences with needs analysis, solution design, product development, implementation, and evaluation. The discussion in this article is confined to the implementation of the developed trainer to improve students critical thinking abilities. Implementation in learning utilizes a quasi-experimental non-equivalent group pretest-post-test design with control and experimental classes, involving 64 respondents from motorcycle engineering vocational high schools selected by purposive sampling. Paired t-test analysis is utilized to ascertain the effectiveness of the trainer in enhancing critical thinking skills. We conclude that the use of appropriate media and teaching methods can foster unique interaction patterns in cognitive dimension formation. Beginning with identifying disturbances and damages, explaining their causes, implementing repair procedures, analyzing repair outcomes, and evaluating the results of disturbances and damages in the motorcycle ignition system.